Mental Health and Suicide of the Doctor in Mexico: An Uncomfortable and Little Explored Topic (Revista de Medicina Clinica, 2021)
The rate of depression, exhaustion and suicide in medical professionals is higher than the general population, however, in our country there is little diffusion, in the same way there are few hospitals that carry out prevention and management strategies. It is known that the number of doctors per capita in Mexico has increased, but this figure is still below the average indicated in the OECD, however, there are few institutions that have strategies to reduce suicide in this group of professionals. This descriptive review refers to mental problems and suicide in doctors in Mexico and in the world, to emphasize this health situation, little disclosed, in the same way we mention certain suggestions made by some authors in the identification, prevention and management timely.
Keywords: Medical residences; mental health; suicid